Enzymatic Preparation of Cello-oligosaccharides Using Bamboo Materials - Hong Chen; Wenbo Chen; Fanqin Yang; Gang Xu; Yin Cao; Shanglian Hu; Bo Zhao (BioResources)
Cello-oligosaccharides (COS) are products of the preliminary hydrolysis of cellulose. They have been the subject of significant research and application potential across various fields, including food, feed, and biotechnology. This study explored an eco-friendly, efficient process for producing COS from bamboo biomass. Subsequently, the optimal hydrolysis conditions using microcrystalline cellulose as the substrate were determined to establish the best process for converting bamboo cellulose into COS. The resulting hydrolyzate was analyzed, with cellobiose content (mg/L) serving as the response variable to identify the optimal conditions for pH, hydrolysis temperature, enzyme addition amount, substrate addition amount, reaction time, and inhibitor addition amount. Finally, various bamboo pretreatment technologies and cellulose hydrolysis methods were integrated to determine the most suitable hydrolysis technology for bamboo cellulose. The results of this study demonstrate that enzymatic hydrolysis can be employed as a production method to convert bamboo cellulose to COS.